Factors affecting the medication literacy of older adults and targeted initiatives for improvement: a cross-sectional study in central China - Chao Mei; Baoli Xu; Xuefeng Cai; Min Wan; Zhigang Zhao; Yongning Lv; Yu Zhang; Ruxu You (Frontiers Media S.A., 2024)
IntroductionThis study explored the state of rational drug use among older adults in central China, aiming to unveil factors influencing their medication literacy and proposing targeted improvement measures.MethodsA cross-sectional study involving 454 participants aged 60 and above was conducted in Hubei province between February 1 and May 30, 2023, with data collected through face-to-face interviews by pharmacists. Multiple logistic regression analysis was conducted to determine factors that affected medication literacy.ResultsOf the 412 valid questionnaires, findings revealed inadequate knowledge of rational drug use among older adults in central China. Those who fully understood (105, 25.49%, OR = 9.349, p < 0.001, 95%CI = 3.884-22.502) or partially understood (228, 55.34%, OR = 3.295, p = 0.002, 95%CI = 1.548-7.013) drug instructions exhibited significantly higher medication literacy than those who did not understand (79, 19.17%). Subsequent research revealed a lack of awareness in reading drug instructions or difficulty in understanding them. Most older adults seldom heard of but exhibited high acceptance of medication guidance services.DiscussionIn conclusion, the ability to comprehend drug instructions significantly influenced the medication literacy of older adults. Initiatives such as revising age-appropriate drug instructions could effectively enhance rational drug use among this demographic.